Thermal Performance of Double Pass Solar Air Heater With Tubular Solar Absorber - Nassr Fadhil Hussein; Sabah T Ahmed; Ali L Ekaid (International Journal of Renewable Energy Development, 2023)
In this investigation, the effect of replacing the conventional solar absorber with a new solar absorber on the thermal performance of a double-pass solar air heater has been studied experimentally and numerically.  Three configurations have been introduced, the first configuration is a double pass solar air heater with a flat plate solar absorber (DPSAHWFP) for the aim of comparison, and the second configuration is a double pass solar air heater with a tubular absorber that includes a set of tubes which are fitted perpendicularly to the direction of airflow (DPSAHWT-1),  and the third configuration is double-pass solar air heater with a tubular absorber that involves set of tubes which are fitted in parallel to the direction of airflow (DPSAHWT-2). The experiments have been carried out under indoor conditions at a constant heat flux equal to 1000 W/m2 and different air mass flow rates (0.01– 0.03 kg/s). The results revealed that the air mass flow rate has a substantial impact compared to the rise in air temperature, hence, the thermal performance of solar air heater is directly proportional to increase air mass flow rate. In addition, the experimental and numerical outcomes indicated that for all air flow rates. The (DPSAHWT-2) offers higher thermal performance as compared to other models, where the maximum effective efficiency has been obtained at 0.03 kg/s equal to 80.9 %. Moreover, (DPSAHWT-2) is more efficient than DPSAHWFP and DPSAHWT-1 by 4.2 % and 9.8 % respectively.